1987
DOI: 10.1139/z87-329
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gut dimensions and capacity of Peromyscus maniculatus relative to diet quality and energy needs

Abstract: Deer mice were maintained on diets diluted with 25, 30, and 45% fibre at 20 °C and on diets of standard laboratory chow at 20, 15, 10, and 5 °C to determine the effects of decreased diet quality and increased energy requirements on the dimensions of the alimentary tract. Weight of the small intestine with contents and of the caecum with contents showed the greatest responses to decreasing diet quality. These increased 59 and 61%, respectively, when diet contained 45% cellulose. Weight of the small intestine wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…Indeed, our results show that mice do increase food intake, at least after 2weeks, in accordance with other studies of chronic cold exposure in mice and other species (Gross et al, 1985;Toloza et al, 1991;Dykstra and Karasov, 1992;Konarzewski and Diamond, 1994;Naya et al, 2005). The primary response of the gut to cold exposure is to augment intestinal size, including increased mucosal mass (Gross et al, 1985;Green and Millar, 1987;Bozinovic et al, 1988;Hammond and Wunder, 1991;Toloza et al, 1991;Dykstra and Karasov, 1992;Konarzewski and Diamond, 1994;Naya et al, 2005; present study). Additionally, there was a non-significant (P=0.069) rise in nominal surface area (after 2weeks cold exposure) that we may not have had the power to detect with statistical confidence.…”
Section: Intestinal Adjustments To a Cold Environmentsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, our results show that mice do increase food intake, at least after 2weeks, in accordance with other studies of chronic cold exposure in mice and other species (Gross et al, 1985;Toloza et al, 1991;Dykstra and Karasov, 1992;Konarzewski and Diamond, 1994;Naya et al, 2005). The primary response of the gut to cold exposure is to augment intestinal size, including increased mucosal mass (Gross et al, 1985;Green and Millar, 1987;Bozinovic et al, 1988;Hammond and Wunder, 1991;Toloza et al, 1991;Dykstra and Karasov, 1992;Konarzewski and Diamond, 1994;Naya et al, 2005; present study). Additionally, there was a non-significant (P=0.069) rise in nominal surface area (after 2weeks cold exposure) that we may not have had the power to detect with statistical confidence.…”
Section: Intestinal Adjustments To a Cold Environmentsupporting
confidence: 93%
“…Further, we hypothesized that intestinal permeability would return to baseline after 2weeks, when intestinal mass and mediated transport mechanisms had compensated for the increased food intake. Two weeks was chosen conservatively as a duration long enough to observe a plateau of changes to gross morphology of the intestine (Green and Millar, 1987;Toloza et al, 1991;Konarzewski and Diamond, 1994). Additionally, at these time points we measured mRNA expression of several tight-junction genes that are hypothesized to be important in regulating permeability to nutrient-sized molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Digestive plasticity has been linked to change in biochemistry, physiology, as well as morphology of the digestive system (Green & Millar, 1987; Sabat, Novoa, Bozinovic, & Martínez del Rio, 1998). The results presented here indicate that gut microflora could also contribute to digestive plasticity and help the host to adapt to a novel dietary niche.…”
Section: Discussionmentioning
confidence: 99%
“…GI flexibility has previously been recorded in response to reduced GI function in lab mice (Kristan, 2002;Kristan and Hammond, 2000;Kristan and Hammond, 2001), providing precedence for such a response. In addition, previous studies have demonstrated that deer mice show marked flexibility in the mass and length of their GI tracts in response to increased energy demands or decreased food quality (Green and Millar, 1987;Hammond and Kristan, 2000;Hammond et al, 2001;Koteja, 1996a).…”
Section: The Journal Of Experimental Biology Schistosome Infection Inmentioning
confidence: 99%
“…I examined a suite of host phenotypic traits, with the goal of establishing how these traits may interact to determine the overall impact of infection on hosts. Deer mice are good experimental subjects because they are natural hosts for this parasite (Malek, 1977;Price, 1931) and because there is a wealth of data available on deer mouse physiology and energetics Chappell and Hammond, 2004;Green and Millar, 1987;Hammond and Kristan, 2000;Hayes, 1989;Hayes and Chappell, 1986;Hill, 1983;Koteja, 1996a;Koteja, 1996b;Millar, 1979;Millar, 1985).…”
Section: Introductionmentioning
confidence: 99%